Self-Assured and Sober: The Relationship Between Maternal Parenting Sense of Competence, Stress, and Alcohol Use - Johnson, Erin; Fellowes, Rebecca; Cant, Kelsie; Hunt, Sally (Frontiers in Global Women's Health, 2022)
Alcohol misuse is widespread, creating serious health and parenting harms. It is important to explore the motivations behind why people drink and the modifiable factors determining severity of the behavior. While alcohol-related research has historically focused on men, the closing gender gap in alcohol consumption highlights a need for targeted research on women. Parenting stress is a commonly reported motivation for maternal drinking. Likewise, parenting stress is associated with parenting sense of competence. However, there is no research connecting parenting sense of competence with alcohol use directly, nor indirectly via moderation of the alcohol and parenting stress relationship. The current study explored these associations and investigated the potential moderation through a questionnaire completed by a sample of 406 mothers. There were significant correlations between all factors, however, parenting sense of competence was not a significant moderator of the parenting stress and alcohol use relationship. Specifically, as a mother’s parenting stress increases, her confidence in the parenting role tends to decline and she is more likely to misuse alcohol. Despite this, variation in parenting sense of competence among women was not significantly correlated with one’s likelihood to drink when coping with stress. Further exploration of these relationships is required, with replication of the current study following the COVID-19 pandemic.